An innovative model of park governance: evidence from Vietnam. Issue 2 (3rd May 2016) - Ly, Tuan Phong; Xiao, Honggen
Abstract : The Vietnamese Special-Use Forests policy introduced in 2006 has transformed the park and protected area governance of the country from being a state responsibility to a multi-component system, under which power is distributed among public and private sectors. This co-existing management model is a special form of concession. This unique management model has long been applied to the management of national parks (NPs) in Vietnam, but studies on the public and private sectors and/or combined management bodies concurrently managing tourism and recreation services in an NP are scarce. Thus, this study investigates the co-existing management model in the Vietnamese park system with the Phong Nha-Ke Bang National Park as a case study. The study describes, analyses and evaluates the model, as well as explains how it works in the Vietnamese park system. This study contributes to knowledge on the governance and management of NPs in Vietnam. Practical applications of the governance model to park management in other regions and countries are also discussed.